Study The Effect of Thiadiazole and Thiazine Derivatives as Antiatherogenic and Antioxidant Agents in Induced Hyperlipidemic Mice (Journal of the College of Basic Education, 2022)
This study conducted to examine the effect of two newly synthesized compounds[3-(5-(ethylthio)-1,3,4-thiadiazol-2-yl)-2,3-dihydro-2-(3-nitrophenyl)benzo[1-3-e] thiazin-4-one (compound I) and 5(4-dimethyl amino) benzylidene amino)-1,3,4-thiadiazole-2-thiol(compound II)] as antiatherogenic and antioxidant agents, In vivo study.